A Descriptive Study to Assess the Risk Factors of Obesity among Housewives Residing at Selected Community, Setting in Kanchipuram District, Tamil Nadu (Medico Legal Update, 2020)
A descriptive study to assess the risk factors of obesity among housewives residing at selected community,setting in Kanchipuram District, Tamil Nadu. The objectives were to assess the risk factors of obesity amongthe housewives to find out the association between assess the risk factors of obesity and selected demographicdata of obesity among the house wives. A non – experimental, descriptive study was conducted.The sampling technique was non-probability, purposive sampling technique with the sample of 30housewives among obesity and Structured questionnaires (SQ) in the form was used to the assess therisk factors obesity among housewives. The variables were assessed the assess the risk factors of obesityamong housewives. Hypotheses were formulated. The level of significance selected was p